Changes in Panulirus cygnus Settlement Along Western Australia Using a Long Time Series - Kolbusz, Jessica; de Lestang, Simon; Langlois, Tim; Pattiaratchi, Charitha (Frontiers in Marine Science, 2021)
The pelagic development stages of many marine invertebrate species dictates their spatial and temporal distribution once reaching their benthic second phase of life. This life cycle is associated with the Western Rock Lobster (Panulirus cygnus) along the coast of Western Australia. Over the past 50 years, the number of puerulus reaching the nearshore reefs after their first nine to eleven months of pelagic life in Western Australia has been monitored. These numbers, collected now at eight sites over the latitudes of the fishery, are indicative of the catchable stock 3 to 4 years into the future. In 2008, the fishery experienced a recruitment failure which lasted for several years before recovering to mean numbers pre-2008. This was associated with spatial and temporal shifts in the patterns of puerulus settlement. Previous research has hypothesized that physical and biological conditions in the south-east Indian Ocean no longer favored their survival. However, this decline has not been attributed to a single process. As the recovery is ongoing, contrasts in the settlement data before and after the decline are not completed. Here we characterize the data using ANOVA and pairwise comparisons to gain a better understanding of the typical patterns after the decline. Our results demonstrate that there has been a significant reduction in puerulus numbers over the first half of the season at all sites post decline. For the sites south of Lancelin there has been a significant reduction in puerulus numbers over the whole season. In addition, sites that show signs of recovery indicate that the majority of settlement occurred in the second half of the season. We anticipate these results to be the starting point for focused research into the environmental changes which may have occurred to generate these shifts in settlement numbers both from a timing and spatial perspective.